Pemetaan Posisi Hilal Terhadap Gunung Agung Dalam Penentuan Awal Bulan Kamariah Di Lokasi Rukyat Pantai Loang Baloq Mataram - Syuhada, Nurnadiyah; Herlina; Bemi Sado, Arino (Universitas Islam Negeri Mataram, 2023)
This study aims to determine the new moon's position towards Mount Agung in mapping at the beginning of the Lunar Month at the Loang Baloq Beach Rukyat location. Loang Baloq Beach has been a routine location for the new moon sightings carried out by the Mataram BMKG team since 2013. However, The hilal is rarely reported to be visible at Loang Baloq Beach. The presence of Mount Agung hinders the condition of the new moon. Based on the study's results, it can be determined that the condition of Loang Baloq Beach does not meet the ideal assessment criteria. This is because the west is not clear at Azimuth 294o46'36.40